Revitalisasi Mobilitas: Pengoptimalan Sistem Penyeberangan Jalan Terintegrasi dengan Metode Hazard Identification Risk Assesment and Determining Control Pada Terminal Petikemas XYZ - Ayyub Ihza Gutawa; Tranggono Tranggono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The low effectiveness of the road crossing system causes frequent accidents and minor incidents that are detrimental to employees and drivers. The large number of accidents that occur can be caused by many factors, including human error, the environment and integrated systems. To be able to measure the possibility and determine a solution to this, XYZ Port applies the HIRADC method which is integrated with the road crossing system. The HIRADC method is an abbreviation for Hazard Identification Risk Assessment and Determining Control. HIRADC is a method in K3 that is used to carry out hazard identification activities, assess the risks posed and determine the form of control for the risks. To achieve superior mobility revitalization, there needs to be an appropriate method for measuring and managing risks in the existing road crossing system. Therefore, the HIRADC method is used to measure all forms of danger and risk in several factors related to optimizing the road crossing system. From the risk analysis, the results obtained were that activities that had a high risk of crossing accidents were crossing traffic management activities. In this activity, there are two dangers that pose a medium risk, namely the danger of vehicles crossing and trailers passing, each at level 9. So it requires more comprehensive risk control efforts to resolve these two dangers.